Impacts of Deep Water Structuring on Seabed Pollution Levels: Evidence from Radiogenic Isotopes (Pb-Sr-Nd) in Surface Sediments Along the Reykjanes Ridge (Southern Iceland) - Karimou, Dia Hantchi; Moussa, Konaté; Ali, Ibrah Landi; Ross, Stevenson K.; Clément, Gariépy (European Scientific Journal, ESJ, 2019)
Significant proportions of debris containing pollutants are present in remote and unknown areas of the deep seabed. Although identified amongst the top threats to marine ecosystem and human health, the mechanisms that particulate materials entered rapidly these deep ocean systems are still matter of debate. This study use depicting radiogenic isotopes (Sr, Nd, Pb) to question the relationship between the seabed sediment contamination levels and ambient stratification in the North Atlantic Ocean. On this basis, we studied sedimentary inputs and related mechanisms from more recent sequences collected at three locations representing different deep-sea hydrodynamics along the Reykjanes Ridge. Sm-Nd concentrations, as well as Sm-Nd-Sr-Pb isotopic compositions, were determined in digested and purified fraction of the sediment cores by Thermal Ionization Mass Spectrometry (TIMS). The Sm-Nd-Sr-Pb data simply reflect the scale of the perturbation of upper part (0-15 cm) of the sequences, which is much more pronounced in east flank than crossing and west bordering ridge areas. The Pb-Pb systematics show that the intensity of water mass mixing modulates degree of contamination and induced the modal transport of detrital components. As consequence of ambient stratification in this region, two major transport processes of pollutant downwards to the sediments are proposed: (i) sediments entrainment in the eastern flank and over ridge axis primarily dominated by vertical flux of particulates controlled by repackage and dislocation by strong mechanical mixing; and (ii) in the west flank, advection of abyssal waters, due to well-stratified mixing layer, provides particulates from the NEADW1 and DSOW.